Staphylococcus aureus: the modern Ghengis Khan - T. D. Chugh (The Journal of Infection in Developing Countries, 2007)
Staphylococcus aureus is the most commonly identified drug-resistant pathogen both in community and hospital-acquired infections with high morbidity and mortality. In spite of intensive search-and-destroy policies in various institutions, it remains invincible globally.